Pendekatan Fengshui dan Ilmu Jawa Kuno dalam Arsitektur - Daryanto Daryanto (Bina Nusantara University, 2013)
House, yard and neighborhood where a person lives affect his life. As legacy of our ancestors, the use of ancient Chinese knowledge of layouting (feng shui) and ancient Javanese knowledge are an approach of eastern culture that needs to be preserved since they are the result of thousand-year wise and sage ancestral experiences. The combination of Chinese and Javanese knowlege help find natural phenomena in relation to the search for life happiness in harmonious balance. Planning the layout of a building needs the study of the characteristics of local condition and prospective residents. Fengshui as one aspect of the approach to natural alignment is used to deal with unbalanced natural or environmental clues around us, which can affect people's lives physically and psychologically. This study aims to identify the relationship between theories and practices as well as to find out to what extent the benefits of feng shui in the design of architecture. The survey results are analyzed by existing ordinances to get evidentiary between theories and practies. Fengshui and ancient Javanese knowledge are some heritages of ancestors’ thousands-year practice in the creating buildings which should be scientifically analyzed and integrated with the science of architecture so that the results obtained will be used in the development of architecture which is useful for occupants.